REDUKSI SENYAWA PENYEBAB RASA PAHIT DALAM PEMBUATAN TEPUNG SUKUN - Widowati, Sri; Amiarsi, Dwi; Nurlaela, Raden Siti (Jurnal Ilmiah Pangan Halal, 2019)
Breadfruit is classified as climacteric fruits, which has fast respiration process, therefor it has short self-life. In an effort to extend the self-life and economic value,  processing intermediate product i.e. flour base to be the right choice. A problem found in the utilization of breadfruit flour is existing a bitter after taste. This study purposes to obtain a processing technology for reducing of bitterness compounds and characterization of breadfruit flour from several regions. Breadfruit flour processing, selected from ten developed methods i.e. breadfruit peeling, washing and cutting pie shapes, blanshing (10 minutes) followed by shredding, soaking (in 0.03% sodium bisulphyte, 1 hour), pressing, drying of the shredded breadfruit to a maximum 12% moisture content, and milling. The best method was applied to produce of breadfruit flour from different regions (Bone, Kep. Seribu, Yogyakarta, Cilacap and Ciputat-South Tangerang). Results show that the best process could reduce of tannin and cyanide acid up to 84% and 93%, respectively. Breadfruit flour characteristics from different regions were vary. The flour yield arround 17-24% of fruit weight or 21-28% of the fruit flesh. Breadfruit flour having ash content of 1.5-2.2% (db); 92-94% carbohydrate (db); in vitro starch digestibility 72.3-87.2%, dietary fiber 6.8-8.1% and 17.7-26.1% amylose.